Promotion of Intestinal Epithelial Cell Turnover by Commensal Bacteria: Role of Short-Chain Fatty Acids - Park, Jung-ha (PLoS One, 2016)
The life span of intestinal epithelial cells (IECs) is short (3–5 days), and its regulation is thought to be important for homeostasis of the intestinal epithelium. We have now investigated the role of commensal bacteria in regulation of IEC turnover in the small intestine. The proliferative activity of IECs in intestinal crypts as well as the migration of these cells along the crypt-villus axis were markedly attenuated both in germ-free mice and in specific pathogen–free (SPF) mice treated with a mixture of antibiotics, with antibiotics selective for Gram-positive bacteria being most effective in this regard. Oral administration of chloroform-treated feces of SPF mice to germ-free mice resulted in a marked increase in IEC turnover, suggesting that spore-forming Gram-positive bacteria contribute to this effect. Oral administration of short-chain fatty acids (SCFAs) as bacterial fermentation products also restored the turnover of IECs in antibiotic-treated SPF mice as well as promoted the development of intestinal organoids in vitro. Antibiotic treatment reduced the phosphorylation levels of ERK, ribosomal protein S6, and STAT3 in IECs of SPF mice. Our results thus suggest that Gram-positive commensal bacteria are a major determinant of IEC turnover, and that their stimulatory effect is mediated by SCFAs.